Effect of Digital Leadership on Career Satisfaction: The Mediating Role of Self-Efficacy in Padang Startups - Rizqi, Hani Amelia; Syahrizal, Syahrizal (Universitas Pamulang, 2025)
The purpose of this research is to examine the impact of digital leadership on career satisfaction among independent employees in startup companies in Padang City, with self-efficacy as a mediating variable. Digital leadership plays a crucial role in shaping employee experiences by providing support, guidance, and motivation through digital tools and leadership approaches. This study explores how digital leadership enhances self-efficacy, which in turn strengthens career satisfaction among independent employees. This research employs a purposive sampling technique, selecting 190 independent employees from various startup companies in Padang City, ranging in age from 19 to 50 years. Data were collected using structured questionnaires and analyzed through the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method to assess the relationships between digital leadership, self-efficacy, and career satisfaction. The findings reveal that digital leadership has a direct positive effect on career satisfaction. Additionally, self-efficacy serves as a significant mediating factor, reinforcing the influence of digital leadership on career satisfaction. Employees who perceive strong digital leadership tend to develop higher self-efficacy, which subsequently enhances their career satisfaction. This study is grounded in Social Cognitive Career Theory (SCCT), which emphasizes self-efficacy as a fundamental component of career development. SCCT suggests that individuals’ belief in their abilities influences their career satisfaction and overall professional growth. In this context, digital leadership acts as an environmental support, fostering employees' confidence and motivation to achieve their career goals.The research provides valuable insights for startup companies to design leadership strategies that enhance self-efficacy and career satisfaction among independent employees. Strengthening digital leadership practices can contribute to employee development, retention, and overall organizational growth in the competitive startup ecosystem.